Probing molecular kinetics using higher-order fluorescence correlation spectroscopy - Abdollah-Nia, Farshad, author; Gelfand, Martin P., advisor; Van Orden, Alan, advisor; Krapf, Diego, committee member; Prasad, Ashok, committee member; Roberts, Jacob, committee member (Colorado State University. Libraries, 2019)
Fluorescence correlation spectroscopy (FCS) is a powerful tool in the time-resolved analysis of non-reacting or reacting molecules in solution, based on fluorescence intensity fluctuations. However, conventional (second-order) FCS alone is insufficient to measure all parameters needed to describe a reaction or mixture, including concentrations, fluorescence brightnesses, and forward and reverse rate constants. For this purpose, correlations of higher powers of fluorescence intensity fluctuations can be calculated to yield additional information from the single-photon data stream collected in an FCS experiment. To describe systems of diffusing and reacting molecules, considering cumulants of fluorescence intensity results in simple expressions in which the reaction and the diffusion parts factorize. The computation of higher-order correlations in experiments is hindered by shot noise and common detector artifacts, the effects of which become worse with increasing order. We introduce a technique to calculate artifact-free higher-order correlation functions with improved time resolution, and without any need for modeling and calibration of detector artifacts. The technique is formulated for general multi-detector experiments and verified in both two-detector and single-detector configurations. Good signal-to-noise ratio is achieved down to 1 μs in correlation curves up to order (2,2). Next, we demonstrate applications of the technique to analyze systems of fast and slow reactions. As an example of slow- or non-reacting systems, the technique is applied to resolve two-component mixtures of labeled oligonucleotides. Then, the protonation reaction of fluorescein isothiocyanate (FITC) in phosphate buffer is analyzed as an example of fast reactions (relaxation time < 10 μs). By reference to an (apparent) non-reacting system, the simple factorized form of cumulant-based higher-order correlations is exploited to remove the dependence on the molecular detection function (MDF). Therefore, there is no need to model and characterize the experimental MDF, and the precision and the accuracy of the technique are enhanced. It is verified that higher-order correlation analysis enables complete and simultaneous determination of number and brightness parameters of mixing or reacting molecules, the reaction relaxation time, and forward and reverse reaction rates. Finally, we apply the technique to analyze the conformational dynamics of DNA hairpins. Previous FCS measurements of DNA hairpin folding dynamics revealed at least three conformational states of the DNA are present, distinguished by the brightness of fluorescent dye-quencher labels. Rapid fluctuations between two of the states occurred on time scales observable by FCS. A third state that was static on the FCS time scale was also observed. We show that conventional FCS alone cannot uniquely distinguish the conformational states or assign their roles in the observed mechanism. The additional information offered by higher-order FCS makes it possible (i) to uniquely identify the static and rapidly-fluctuating states; and (ii) to directly measure the brightnesses and populations of all three observed states. The rapid fluctuations occurring on the FCS time-scale are due to a reversible reaction between the two lowest brightness levels, attributed to the folded and random-coil conformations of the DNA. The third state, which is the brightest, is attributed to spatially extended unfolded conformations that are isolated from the more compact conformations by a substantial energy barrier. These conformations attain a maximum equilibrium population of nearly 10% near physiological temperatures and salt concentrations.
Keywords: high-order fluorescence correlation spectroscopy; nucleic acids; higher-order fluorescence correlation spectroscopy; conformational dynamics; molecular kinetics in solution; DNA